DNA barcoding reveals that injected transgenes are predominantly processed by homologous recombination in mouse zygote - Smirnov, Alexander (Nucleic Acids Res, 2020)
Mechanisms that ensure repair of double-strand DNA breaks (DSBs) are instrumental in the integration of foreign DNA into the genome of transgenic organisms. After pronuclear microinjection, exogenous DNA is usually found as a concatemer comprising multiple co-integrated transgene copies. Here, we investigated the contribution of various DSB repair pathways to the concatemer formation. We injected mouse zygotes with a pool of linear DNA molecules carrying unique barcodes at both ends and obtained 10 transgenic embryos with 1–300 transgene copies. Sequencing the barcodes allowed us to assign relative positions to the copies in concatemers and detect recombination events that occurred during integration. Cumulative analysis of approximately 1,000 integrated copies reveals that over 80% of them underwent recombination when their linear ends were processed by synthesis-dependent strand annealing (SDSA) or double-strand break repair (DSBR). We also observed evidence of double Holliday junction (dHJ) formation and crossing over during the concatemer formations. Sequencing indels at the junctions between copies shows that at least 10% of DNA molecules introduced into the zygotes are ligated by non-homologous end joining (NHEJ). Our barcoding approach, verified with Pacific Biosciences Single Molecule Real-Time (SMRT) long-range sequencing, documents high activity of homologous recombination after DNA microinjection.